The Impact of Using Visual Grammar on Iraqi EFL Secondary Students’ Performance - Sultan , Hellah; Sultan , Amra I. (International Journal of Membrane Science and Technology, 2023)
This study sheds light on the aspect of visual grammar, which it’s teaching in Iraq has not received any attention in educational institutions or within the classroom curricula, so it aims at measuring the impact of using visual grammar on EFL secondary students’ performance.